Synthesis and Characterization of Corn Husk (Zea Mays L.) Cellulose Using Microwave-Assisted Extraction (MAE) - Nor Pana Yupa; Tetty Kemala; Henny Purwaningsih (Jurnal Kimia Sains dan Aplikasi, 2023)
This research focuses on synthesizing cellulose from corn husks using microwave-assisted extraction (MAE), which aims to produce cellulose from corn husks through liquefaction, delignification, and bleaching processes. The total time required is only 14 minutes, thus shortening the process time. This study used three power variations: 450 W, 600 W, and 800 W. The results showed that the optimum conditions occurred at 800 W power. Hence, the higher the power caused the high cellulose content obtained, which amounted to 75.23% and decreased the lignin value to 15.78%, along with the increase in microwave power. FTIR analysis also confirmed the cellulose results obtained and indicated that the lignin groups were weakened or lost. Furthermore, morphological analysis of cellulose fibers by SEM showed that the surface of cellulose fibers was rough, oval, and irregular due to cracks caused by erosion. Then, the result of cellulose crystallinity using XRD was 45.8%. Compared to conventional methods, microwave-assisted cellulose synthesis exhibits better and more promising potential. This is because microwave radiation can be used to improve process time efficiency and achieve higher yields. Moreover, the proposed method is easier, faster, and straightforward.